Coumarin: A Privileged Scaffold for the Design and Development of Antineurodegenerative Agents. (16th September 2015) - Jameel, Ehtesham; Umar, Tarana; Kumar, Jitendra; Hoda, Nasimul
Abstract : Drug development for neurodegenerative diseases (NDs) is foremost task for the medicinal chemists in the 21st century. Coumarins are exemplary of an assorted and aptitudinally useful set of drugs. Coumarins play a momentous role in several pharmacological and medicinal aspects. Its analogues are anticipated to play a significant role in the development of new therapeutic leads for NDs. Their promising applications in the field of ND medication are exemplified by clinical candidates such as nodakenin that have been potent for demoting memory impairment. Apart from ND, clinically used anticoagulant warfarin, anticoagulant dicoumarol, and antibiotic coumermycin, novobiocin and chartesium grab the interest of researchers in coumarins. It would be worthwhile to look at the different biological processes that could cause neurodegeneration, thereby establishing a link with distinct coumarin derivatives to serve the purpose of medication. This review undertakes estimation of the wide spectrum of studies focusing coumarin to the domain of drug research for ND. Herein, we search for multitarget coumarin‐based inhibitors and their scope for NDs. Future challenges in coumarin‐based drug development have been discussed, and emphases have been laid on the future perspectives of coumarins as possible drugs in the future for the treatment of NDs. Abstract : Coumarins are exemplary of an assorted and aptitudinally useful set of drugs. Their promising applications in the field of neurodegenerative medication are exemplified by clinical candidates such as nodakenin that have been potent for demoting memory impairment.